2015
DOI: 10.1007/s11199-015-0492-y
|View full text |Cite
|
Sign up to set email alerts
|

Planning to Have It All: Emerging Adults’ Expectations of Future Work-Family Conflict

Abstract: This study assessed college students' anticipated work-family conflict (family-impacting-work and workimpacting-family), and the family-altering and work-altering strategies they plan to employ to relieve that conflict. Undergraduates (N=121) from two universities in the southeastern U.S. were surveyed and differences between the genders were tested. There were no significant gender differences in total conflict, but women anticipated more family-impacting-work conflict, while men anticipated greater work-impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 44 publications
(67 reference statements)
2
29
2
2
Order By: Relevance
“… Salary compensation: Salary has traditionally been an important attribute for job choice. When entering the construction industry, individuals are faced with the reality of a high income and a long working week with a low work-life balance [9]. When an employee has already fulfilled these needs and is searching to fulfil 'higher-order' needs, the individual may seek to embrace a greater work-life balance lifestyle [17].…”
Section: Factors Influencing Work-life Balancementioning
confidence: 99%
See 1 more Smart Citation
“… Salary compensation: Salary has traditionally been an important attribute for job choice. When entering the construction industry, individuals are faced with the reality of a high income and a long working week with a low work-life balance [9]. When an employee has already fulfilled these needs and is searching to fulfil 'higher-order' needs, the individual may seek to embrace a greater work-life balance lifestyle [17].…”
Section: Factors Influencing Work-life Balancementioning
confidence: 99%
“…The male-dominated nature of the construction industry makes the culture of 'work hard and play hard' the norm of the industry [7,8]. The industry is also highly competitive, forcing construction organisations to reduce their labour cost, operate with low profit margin, and work with unreasonable time constraints [8,9]. This culture in the Australian construction industry drives employees to work longer hours than contractually obligated.…”
Section: Introductionmentioning
confidence: 99%
“…Personal beliefs that represent the aspects of self that make one an individual (personal identity) or that are rooted in various group memberships (social identity) are known to play an important role in directing and regulating various learning outcomes, including career-related aspirations and goals (e.g., Barreto & Frazier, 2012;Capobianco, French, & Diefes-Dux, 2012;Oyserman & Destin, 2010). Of these beliefs, those related to work and family are among the many factors that influence the choice of engineering as a vocation (e.g., Hawks & Spade, 1998), with the significance of these identities increasing as students consider their transition from academic programs to the professional workforce (e.g., Amelink & Creamer, 2010;Cech et al, 2011;Coyle et al, 2015;Hawks & Spade, 1998). The rationale for linking work and family identities and engineering identity in the framework for this study is grounded in the theories of possible selves (Markus & Nurius, 1986), self-competence (Marsh, 1992), and gender identity (Egan & Perry, 2001).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Theories of gender role socialization posit that traditionally gendered social roles influence the recruitment to and retention of men and women in different careers and professions (e.g., Cech, ; Correll, ; Hartman & Hartman, ; Settles, ), and research has found that personal beliefs and attitudes about work and family have important relationships with professional identity (e.g., Amelink & Creamer, ; Cech, Rubineau, Silbey, & Seron, ; Coyle, Van Leer, Schroeder, & Fulcher, ; Hawks & Spade, ; Jackson, Gardner, & Sullivan, ). Specific to the STEM fields, “engineering has always occupied a central position in the debate about recruitment and retention practices, especially for women” (Dutta, , p. 326) because substantially fewer women than men enroll in engineering programs (Cech, ; Lerdpornkulrat, Koul, & Sujivorakul, ).…”
Section: Introductionmentioning
confidence: 99%
“…일가정 다중역할에 대해 미리 신중한 계획 을 세우고 전략을 수립하는 것은 갈등을 완화하고 삶의 만족에 긍 정적인 영향을 주는 대처전략이 될 수 있다 (Choi, Y. J., 2010;Steffy & Jones, 1988). 그러나 현재 대학의 진로교육은 직업(일) 선택과 준비에 초점이 맞추어져 있으며 (Kim et al, 2016), 실 제 대학생들의 진로계획 역시 일가정양립 상황에 대한 고려 없이 직업(일) 중심으로 세우는 것으로 나타났다 (Coyle et al, 2015;Hwang et al, 2014;Spade & Reese, 1991). 따라서 실질적인 진로를 준비하는 대학 시기에 미래 일과 가정생활을 신중하게 고 려하여 진로를 계획하는 통합적 관점의 진로 설계가 필요하다.…”
unclassified